Concentration For Independent Permutations. - McDiarmid, C (2002)
An extended version of a concentration inequality based on the work of Talagrand is presented. The given inequality concerns a family of independent random permutations. One particular use is for analyzing randomized methods for graph coloring that involve randomly relabelling the colors used in different parts of the graph.